Research on Evaluation Indicators for Humanistic Ward Rounds in Hospice Care Institutions - Yiwen MAO; Yumiao WU; Yilei LIU; Jun WU; Yikai MI; Yongxing SHI (Yixue yu zhexue)
Firstly, based on literature research and a Delphi consultation, the opinions of 15 domestic experts in the field of hospice care services were summarized and sorted out. The evaluation indicators for humanistic ward rounds in hospice care service institutions were constructed, consisting of 4 primary indicators, 13 secondary indicators, and 22 tertiary indicators, with an expert consistency coefficient of 0.654 (P＜0.05). Secondly, a survey was conducted on 120 hospice care service personnel from 13 institutions conducting humanistic ward rounds to evaluate the feasibility of the indicator system. The Cronbach's alpha coefficient for 22 indicators was 0.820, and the Guttman halving coefficient was 0.844. The CVI values for all tertiary indicators exceeded 0.78. The evaluation indicator system demonstrated good reliability, validity, and feasibility, providing a solid foundation for further designing specific evaluation tools and promoting standardized implementation of humanistic ward rounds in hospice care.